[tex] \frac{7}{8} - ( \frac{3}{4} - \frac{5}{6}) + 1 \frac{1}{2} = \frac{3 \times 3}{4 \times 3} - \frac{5 \times 2}{6 \times 2} = \frac{9}{12} - \frac{10}{12} = \frac{9 - 10}{12} = \frac{7}{8} - ( - \frac{1}{12}) + 1 \frac{1}{2} = \frac{7}{8} - ( - \frac{1}{12}) + \frac{1 \times 2 + 1}{2} = \frac{7}{8} - ( - \frac{1}{12}) + \frac{3}{2} = \frac{7}{8} + \frac{1}{12} + \frac{3}{2} = \frac{7 \times 3}{8 \times 3} + \frac{1 \times 2}{12 \times 2} + \frac{3 \times 12}{2 \times 12} = \frac{21}{24} + \frac{2}{24} + \frac{36}{24} = \frac{21 + 2 + 36}{24} = \frac{59}{24} = 2 \frac{11}{24} [/tex]